PENGARUH MOTIVASI DAN KEMANDIRIAN BELAJAR TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SISWA DI MASA PANDEMI COVID - 19 - Siprianus Jewarut; Defriana Nidriawati (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2022)
This study aims to determine the effect of student learning motivation and independence on understanding mathematical concepts during the covid-19 pandemic. The hypotheses of this study are 1) The interactive effect of motivation and independent learning together on the ability to understand mathematical concepts. 2) The significant effect of motivation on understanding mathematical concepts. 3) The significant effect of learning independence on the ability to understand mathematical concepts. The research was conducted by survey method using regression data analysis. The population is class VII SMP Negeri in Kemayoran, Central Jakarta with a sample size of 88 students. The research instrument used is a test of understanding mathematical concepts in the form of multiple choice with 30 options. Questionnaire of learning motivation and learning independence. The results of hypothesis testing obtained the following conclusions: 1) There is a significant effect of learning motivation and learning independence together on understanding mathematical concepts. This is evidenced by the value of Sig. = 0.000 <0.05 and F_hitung = 1052.654. 2) There is a significant effect of learning motivation on understanding mathematical concepts. This is evidenced by the value of Sig. = 0.000 < 0.05 and t_count = 4.064. 3) There is a significant effect of independent learning on the understanding of mathematical concepts. This is evidenced by the value of Sig. = 0.006 < 0.05 and t_count = 2.843.